2010
DOI: 10.1107/s1600536810015655
|View full text |Cite
|
Sign up to set email alerts
|

3-Aminophenylboronic acid monohydrate

Abstract: In the title compound, C6H8BNO2·H2O, the almost planar boronic acid mol­ecules (r.m.s. deviation = 0.044 Å) form inversion dimers, linked by pairs of O—H⋯O hydrogen bonds. The water mol­ecules link these dimers into [100] chains by way of O—H⋯O hydrogen bonds, and N—H⋯O links generate (100) sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The aromatic carbons give resonances in overlapped areas of the NMR spectrum with chemical shift values from 100 to 150 ppm [54,55]. The calculated and experimental 13 162.64, 141.87, 130.07, 129.80, 119.65 and 116.77 ppm, respectively. The C 4 atom has smaller chemical shifts (both experimental and theoretical) than the other ring carbon atoms, due to shielding effect which the non-electronegative property of B(OH) 2 group.…”
Section: Nmr Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…The aromatic carbons give resonances in overlapped areas of the NMR spectrum with chemical shift values from 100 to 150 ppm [54,55]. The calculated and experimental 13 162.64, 141.87, 130.07, 129.80, 119.65 and 116.77 ppm, respectively. The C 4 atom has smaller chemical shifts (both experimental and theoretical) than the other ring carbon atoms, due to shielding effect which the non-electronegative property of B(OH) 2 group.…”
Section: Nmr Spectrummentioning
confidence: 99%
“…The molecular structures of phenylboronic acid and its derivatives have been studied many authors for years [6][7][8][9][10][11][12][13][14][15]. Rettig and Trotter [6] studied crystal and molecular structures of phenylboronic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shimpi et al [20] reported the crystal structures of 4-chloro-and 4-bromophenylboronic acids and hydrates of 2-and 4-iodophenylboronic acid in two different forms, which were characterized by single-crystal X-ray diffraction methods. The molecular and crystal structures of 3-Formylphenylboronic acid [21] and 3-aminophenylboronic acid monohydrate [22] were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the APBA treatment was carried out in a 0.1 M HCl solution containing 1 mM APBA and an equimolar amount of NaNO 2 via voltage cycling between 0 and −0.6 V for one cycle at a scan rate of 50 mV/s. The increments (Δr), 0.13 nm and 0.27 nm, suggest that the HOPG becomes covered with a submonolayer of APBA and Ru(bpy) 2 (phendione) 2+ and the reaction stoichiometry between APBA and Ru(bpy) 2 (phendione) 2+ is 1 : 1 in terms of molar ratio, estimated under the assumption that the molecular sizes of the compounds are approximately proportional to the cube roots of their cell volumes (760Å 3 for APBA [15] and…”
Section: Resultsmentioning
confidence: 99%